INNOVATIVE POTENTIAL OF STRUCTURAL CONVERGENCE OF THE RUSSIAN ECONOMY - M. A. Gasanov; A. V. Zhavoronok; M. A. Klimovich (Вестник университета)
A structural analysis of macrodynamics has been carried out under conditions of a deepening structural crisis and an increase in the cyclic instability of the Russian economy, taking into account world trends of the new industrial revolution and technological transition. The presence of an innovative pause, technological lag and growing contradictions gain the background of increasing recessionary tendencies has been revealed. Theoretical concepts, a scientifically based mechanism and tools for the deployment of innovative technologies, their transfer and diffusion in the basic sectors of the Russian economy, as well as the launch of a mechanism for the structure formation of the newest science-intensive sectors of the economy have been elaborated and proposed.